Application of pressure wire in carotid artery stenting - Shi-bo WANG; Xu-dong LI; Qiang JIA; Jing HAN; Tao FENG; Yi-mu FAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2013)
Background Nowadays, critical carotid stenosis lacks appropriate treatment standards, and carotid artery stenting (CAS) needs more direct guidance. This study aims to investigate the possibility of applying pressure wire in CAS, and the guidance of pressure gradients in choosing indications of CAS. Methods From May 2012 to October 2012, 32 consecutive cases with carotid stenosis undergoing CAS were enrolled. Preoperative and postoperative carotid ultrasound and CT perfusion imaging were performed, and intraoperative measurements of endovascular pressure gradients before and after stent implantation were recorded to evaluate intracranial circulation compensation. Results Preoperative carotid ultrasound showed the rate of stenosis in 32 cases was ≥ 70% or nearly total occlusion. Doppler measurement of peak systolic velocity (PSV) of the stenosed vessel ranged 184-718 cm/s. Digital subtraction angiography (DSA) examination showed the stenosis rates were 50%-70% in 7 cases, 70%-90% in 16 and > 90% in 9. The coincidence rate of carotid ultrasound and DSA was 84.38% (27/32), and the acquisition rate of intraoperative carotid pressure gradients was 100% . Pressure gradients before stent implantation were 10-92 mm Hg, with an average of (41.45 ± 25.50) mm Hg, and pressure gradients after stent implantation were 0-15 mm Hg, with an average of (3.44 ± 3.47) mm Hg. DSA revealed 4 cases with good intracranial circulation compensation and 28 cases with poor intracranial circulation compensation. Conclusion Pressure wire can be safely and effectively used in CAS to acquire pressure gradients between the two ends of stenosis segment. For carotid artery stenosis patients lacking of intracranial circulation compensation, pressure gradients become higher as stenosis rate increases within a certain range. Therefore, CAS for stenosis with lower pressure gradients should be reconsidered.